A new species of the cardinalfish genus Apogon (Teleostei, Apogonidae) from the southern Red Sea and Indian Ocean with comments on phylogenetic relationships within the Apogonini - Gon, Ofer; Bogorodsky, Sergey V.; Mal, Ahmad O.; Alpermann, Tilman J. (Zootaxa, 2020)
Apogon fugax is described as a new species of cardinalfishes based on a specimen trawled off Jizan (Saudi Arabia), southern Red Sea, at a depth of 60–67 m; two specimens trawled off southwest of Ayeyarwady Delta, Myanmar, at 54–129 m; and two specimens trawled off Western Australia at 166 m. The new species shares characters with the modified ‘talboti look-alikes’ species group (i.e., A. caudicinctus, A. dianthus and A. soloriens) as well as A. rubrifuscus and A. deetsie (both previously also assigned to the latter species group) in having two supraneurals, 12 pectoral-fin rays (13 rays in A. soloriens), and an enlarged, membranous, ventral preopercular edge. Molecular phylogenetic analysis of the apogonid tribe Apogonini, however, revealed that A. fugax n. sp. and its most closely related congeners, A. deetsie and A. rubrifuscus, form a separate phylogenetic clade unrelated to that formed by the ‘talboti look-alikes’ species group that is part of the A. unicolor species group. Apogon fugax n. sp. is distinguished from the species of the ‘talboti look-alikes’ species group, A. deetsie and A. rubrifuscus, in having a large head (2.2–2.4 in SL versus 2.4–2.8 in SL), longer first dorsal-fin spine (1.7–2.0 versus 2.7–4.0 in length of the second spine), and in their gill rakers count (developed gill rakers on the first gill arch 11–12 versus 8–9 in A. soloriens and 13–20 in the other four species).